PERANAN KELUARGA, MASYARAKAT DALAM PENDIDIKAN ISLAM: The Role Of Family, Society In Islamic Education - Fahrul Fahrudin; Zaenal Arifin Arifin (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Abstract This study uses a descriptive methodology with data collection from several literatures. Data analysis is carried out by selecting the appropriate articles. The results of the research are that it is said that the main education that occurs and takes place in this family is very influential on the life and education of the next child. The role of the community is also the most decisive in Islamic education where the child knows the environment, whether good or bad, the environment will have an impact on the role of Islamic education. Conclusion Family, school and community relations can run harmoniously and dynamically, so it can help in developing the role of the family, talents and interests of children so that children can grow and develop so that the educational process will be carried out productively, effectively, efficiently and successfully so as to produce quality outputs intellectually, spiritually and socially. Keyword : Islamic education, family, society, environment